2009
DOI: 10.1111/j.1440-1681.2009.05213.x
|View full text |Cite
|
Sign up to set email alerts
|

Carotid body potentiation induced by intermittent hypoxia: Implications for cardiorespiratory changes induced by sleep apnoea

Abstract: 1. The most usual form of chronic hypoxia in humans is the intermittent hypoxia resulting from obstructive sleep apnoea (OSA). The OSA syndrome is a highly prevalent sleep breathing disorder that is considered an independent risk factor for hypertension and cardiovascular diseases. Endothelial dysfunction, oxidative stress, inflammation and sympathetic activation have been proposed as potential mechanisms involved in the onset of the hypertension. However, evidence for a unique pathogenic mechanism has been di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
103
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 73 publications
(106 citation statements)
references
References 58 publications
3
103
0
Order By: Relevance
“…The increased formation of 3-nitrotyrosine indicates that the carotid body tissue is continuously exposed to oxidative stress during the intermittent hypoxic exposure. In addition, we found that a correlation between the marked increase of 3-nitrotyrosine immunoreactivity in the carotid body exposed to intermittent hypoxia and the enhanced carotid chemosensory responses to acute hypoxia (Del Rio et al, 2011), supporting and extending the idea that oxidative-nitrosative stress plays a critical role in the CB chemosensory potentiation (Iturriaga et al, 2009. In OSA patients, Jelic et al, (2008) found that the expression of 3-nitrotyrosine in endothelial cells was greater than controls subjects, indicating that the oxidative stress contributes to the endothelial dysfunction caused by the intermittent hypoxia.…”
Section: Reactive Oxygen and Nitrogen Speciessupporting
confidence: 62%
See 2 more Smart Citations
“…The increased formation of 3-nitrotyrosine indicates that the carotid body tissue is continuously exposed to oxidative stress during the intermittent hypoxic exposure. In addition, we found that a correlation between the marked increase of 3-nitrotyrosine immunoreactivity in the carotid body exposed to intermittent hypoxia and the enhanced carotid chemosensory responses to acute hypoxia (Del Rio et al, 2011), supporting and extending the idea that oxidative-nitrosative stress plays a critical role in the CB chemosensory potentiation (Iturriaga et al, 2009. In OSA patients, Jelic et al, (2008) found that the expression of 3-nitrotyrosine in endothelial cells was greater than controls subjects, indicating that the oxidative stress contributes to the endothelial dysfunction caused by the intermittent hypoxia.…”
Section: Reactive Oxygen and Nitrogen Speciessupporting
confidence: 62%
“…The enhance carotid chemosensory responses to hypoxia has been associated to increased levels of reactive oxygen species , Iturriaga et al, 2009, Del Rio et al, 2010 and endothelin-1 within the CB (Rey et al, 2006, Pawar et al, 2009, but it is possible that pro-inflammatory cytokines, which increased in the plasma of OSA patients (Lavie 2003, Jelic et al, 2008 may also contributes to the enhanced carotid body chemosensory responses to acute hypoxia (Iturriaga et al, 2009;Del Rio et al, 2011). Although some studies addressed the effects of intermittent hypoxia on transmitter production and release in the carotid body, very little is known on the functional significance of the role played by the neurotransmitters in the carotid body chemosensory potentiation induced by intermittent hypoxia (See for review Kumar, 2011).…”
Section: Mechanisms Underlying the Potentiation Of Carotid Body Chemomentioning
confidence: 99%
See 1 more Smart Citation
“…In adults, this depends on the recurrent activation of peripheral chemoreceptors and is prevented by bilateral carotid body denervation during exposure (12,30), and following chemical sympathetic denervation (13). This is accompanied by an enhanced activity of peripheral chemoreceptors (23,48), chronic sympathetic activation (11,29,31,44), blunted baroreflex responses (3,31), and functional changes in the vascular bed (7). Whether similar changes are also induced by exposure to neonatal hypoxia in newborns and have longlasting effects remains to be documented.…”
Section: Respiratory and Hemodynamic Variables In Normoxia In Controlmentioning
confidence: 99%
“…The primary oxygen sensors in the carotid body are the glomus cells, which are in synaptic contact with the nerve terminals of the chemosensory petrosal neurons [31,40,42]. The current model of chemoreception states that hypoxia induces the inhibition of voltage-independent tandem pore domain potassium channels (TASK K + ), leading to the depolarization of the glomus cells, the entry of Ca 2+ through L-type Ca 2+ channels, and the subsequent release of excitatory transmitters (Acetylcholine and adenosine triphosphate), which increases the discharges of the nerve endings of the petrosal chemosensory neurons [40,42]. Recently, we found that chronic intermittent hypoxia potentiates the hypoxic inhibition of the TASK-like K + channel currents in glomus cells from intermittent hypoxia rats.…”
Section: Moreover Fletcher Et Al [See Inmentioning
confidence: 99%